Dosimetric correlation of acute and late toxicities in high-risk prostate cancer patients treated with three-dimensional conformal radiotherapy followed by intensity modulated radiotherapy boost - Rakesh Kapoor; Anshuma Bansal; Narendra Kumar; Arun S Oinam (Indian Journal of Urology, 2016)
Introduction: In prostate cancer, higher radiation doses are often related to higher local control rates. However, the clinical effect of these higher doses on normal tissue toxicities is generally overlooked. We dosimetrically analyze sequential intensity modulated radiotherapy (IMRT) plans in high-risk prostate cancer patients and correlate them with acute and late normal tissue toxicities. Materials and Methods: Twenty-five high-risk prostate cancer patients were planned with three-dimensional conformal radiotherapy to a dose of 50 Gy delivered in 25 fractions in 5 weeks, followed by seven-field IMRT boost, to a dose of 24 Gy delivered in 12 fractions in 2.5 weeks, along with hormonal therapy. Acute and late toxicities were analyzed using Radiation Therapy Oncology Group toxicity criteria. Student's t-test was used for correlating doses received by normal tissues with toxicity grade. Five-year disease-free survival (DFS) and biochemical relapse-free survival (RFS) were evaluated using Kaplan–Meier analysis. Results: Median follow-up of patients was 65 months. Of 25 patients, two developed acute Grade 2 rectal toxicity. Only 1 patient developed acute Grade 2 bladder toxicity. Late Grade 2 and 3 rectal toxicity was seen in 2 and 1 patient, respectively. Late Grade 2 and 3 bladder toxicity was seen in 1 patient each. Grade 2 or more acute rectal toxicity correlated significantly with rectal volume receiving >70 Gy (P = 0.04). The 5-year DFS and biochemical RFS was 70.2% and 79.2%, respectively. One patient failed locally and seven failed at distant sites. Conclusion: Sequential IMRT with a dose of 74 Gy and maximum androgen blockade is well tolerated in high-risk patients in Indian setup with adequate control rates.